2016
DOI: 10.3389/fmicb.2016.00911
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Staphylococcus aureus Isolated from Retail Meat in Riyadh, Saudi Arabia

Abstract: Limited data exist from the Gulf Cooperation Council states on the prevalence and population dynamics of Staphylococcus aureus colonizing livestock or contaminating retail meat. This study was designed to determine the presence and genetic characteristics of Staphylococcus aureus isolated from raw retail meat sold in Riyadh, Saudi Arabia. Over a period of 9 months, different raw retail meat types were aseptically processed using the double broth enrichment technique, characteristic colonies from chromogenic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 30 publications
(45 reference statements)
10
51
3
Order By: Relevance
“…MRSA has been widely reported to be associated with milk in different parts of the world . In another study from Riyadh, MRSA was reported in retail meat . This study also found that the camel meat contains the highest number of MRSA.…”
Section: Resultssupporting
confidence: 54%
“…MRSA has been widely reported to be associated with milk in different parts of the world . In another study from Riyadh, MRSA was reported in retail meat . This study also found that the camel meat contains the highest number of MRSA.…”
Section: Resultssupporting
confidence: 54%
“…Two isolates (RUH-2 and RUH-71) were from patients with sepsis and wound infection, respectively, while the other 2 (RUH-98 and RUH-99) were from retail camel meat. S. aureus identification and confirmation of methicillin resistance was performed as previously described 6,7. Genomic DNA was extracted using Qiagen DNA isolation kit (Qiagen, Hilden, Germany) in accordance with manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…While whole genome sequencing data are available for CC15-MSSA, there are, to the best of our knowledge, no publications on the genomic data for the rare CC15-MRSA. Recently, we reported the first identification of CC15-MRSA from clinical infections and retail meat products in the Middle East 6,7. In light of the emergence of CC15-MRSA in our setting and to provide much-needed insight into the genetic make-up of this rare MRSA clone, we have carried out whole genome sequencing of these isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Although detection and genotyping of S. aureus was common in diseased poultry (Richter et al, 2012; ArgudĂ­n et al, 2013; Monecke et al, 2013; Kraushaar et al, 2016) and from poultry meat (Boost et al, 2013; Buyukcangaz et al, 2013; Krupa et al, 2014; Abdalrahman et al, 2015; Kim et al, 2015; Sallam et al, 2015; Bortolaia et al, 2016; Kraushaar et al, 2016; Raji et al, 2016), characterization data of S. aureus isolates from healthy turkeys and broilers are still widely lacking.…”
Section: Introductionmentioning
confidence: 99%